A family of anti-swing motion controllers for 2D-cranes with load hoisting/lowering. (1st November 2019) - Miranda-Colorado, Roger; Aguilar, Luis T.
Graphical abstract: Highlights: We proposed a novel scheme for choosing a design function for disturbance attenuation. The proposed methodology attenuates the payload oscillations. The algorithm also improves the performance according to the desired motion. We introduce numerical and real-time experiments developed in a laboratory crane prototype. Abstract: This paper presents a methodology for designing controllers that attenuate the payload swing angle in two-dimensional overhead crane systems with varying rope length. The proposed scheme is based on the proper construction of a design function, which combines the coordinate of the translational motion of the crane with that corresponding to the swing angle. The proposed methodology shows how to design a family of functions that can be used not only to attenuate the swing angle but also to follow a desired motion. Then, the controller is implemented in combination with a trajectory design stage based on S-curves. The proposed scheme is compared with a controller with a proportional derivative structure and an adaptive controller. Numerical and experimental results validate the proposed methodology and show the effectiveness of the proposed controller even when the system is being affected by state estimation errors and external disturbances.